Isolation and identification of Saccharomyces cerevisiae for fermentation of rice polishing in Livestock feeding - SHARIF,MUHAMMAD (2020)
Abstract Biomass of Saccharomyces cerevisiae wasenhancedin rice polishing by fermentation to increase protein contents of feedfor its use in livestock. Broth culture of Saccharomyces cerevisiae (2.6×108CFU/mL) was prepared from culture obtained by continuous streaking. The isolated culture was identified morphologically by Gram staining and confirmed by biochemical characteristics. Rice polishing was sieved to remove larger particles. Then it was distributed to 4 treatments in triplicates. Treatments were represented as rice polishing (RP), rice polishing plus Saccharomyces culture (RPSC), rice polishing plus ammonium sulphate (RPAS), rice polishing plus Saccharomyces culture plus ammonium sulphate (RPSCAS).Fermentation was provided for 144 hours at 320C,while samples were collected after every 24 hours. Samples were dried, ground and subjected to proximate analysis. It was observed that protein content was increased from 11% to 21.51% and maximum increment was obtained after 144 hours of incubation in RPSC treatment. Ether extract and ash were increased from 14% and 10% to 16.96% and 11.11% in RPSCAS respectively. A significant reduction in neutral detergent fiber was observed after fermentation. It is concluded that Saccharomyces cerevisiae has potential to improve mineral and protein contents of rice polishing by fermentation process with or without addition of nitrogen source.